2020
DOI: 10.1159/000506835
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamics Are Not Affected by the Size of the Patent Ductus Arteriosus

Abstract: Introduction: Although patent ductus arteriosus (PDA) has been implicated to play a role in the development of cerebral ischemia and intraventricular hemorrhage (IVH) through a cerebral steal phenomenon, there is conflicting data on the impact of PDA size on cerebral blood flow (CBF). Cerebral autoregulation is the brain's innate protective mechanism to maintain constant CBF despite changes in blood pressure, and it is unclear if it is influenced by PDA hemodynamics. Objective: To delineate the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Cortisol is a stress hormone secreted by the adrenal cortex, which can be affected by infection, asphyxia, and other critical conditions (14). Previous studies used gestational age and prenatal dexamethasone as matching conditions, and found that the level of cortisol was related to the occurrence of PDA in premature infants (15,16). However, the influence mechanism of cortisol on the closure of the arterial catheter is unclear (17).…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol is a stress hormone secreted by the adrenal cortex, which can be affected by infection, asphyxia, and other critical conditions (14). Previous studies used gestational age and prenatal dexamethasone as matching conditions, and found that the level of cortisol was related to the occurrence of PDA in premature infants (15,16). However, the influence mechanism of cortisol on the closure of the arterial catheter is unclear (17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of confounders may have influenced the results of these studies. Kim et al designed a cohort study including newborns with GA <29 weeks to assess the relation between the size of PDA and cerebral hemodynamics within the 1st week of life ( 45 ). They indicated that cerebral hemodynamics was found to be stable regardless of the size of PDA in those premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…CrCP gradually increases at a rate of 1.4 mmHg per week in premature infants [4]. Moreover, CrCP in infants has been used to assess changes in cerebral perfusion due to patent ductus arteriosus and predict intraventricular haemorrhage [5,6]. However, insertion of an arterial line is invasive and di cult, especially in premature infants.…”
Section: Introductionmentioning
confidence: 99%